Screening of tomato varieties for resistance to major fungal diseases and bacterial wilt - Tsetskladze, Ts.; Sikharulidze, Z.; Muradashvili, M.; Sikharulidze, K. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2018)
The resistance of local and introduced tomato varieties to early blight (Alternaria solani Sorauer) and late blight (Phytopthora infestans (Mont.) de Bary) were evaluated in the field and to bacterial wilt (Ralstonia solanacearum) were tested under artificial infection in greenhouse conditions. Three varieties (De-brao krasnii, De-brao Rozovii and Sultan F1) showed the moderate resistance to early blight, while the only two varieties (De-brao krasnii and De-brao Rozovii) were moderate resistant to late blight. The remaining samples showed susceptibility to disease. The tested varieties showed a different degree of resistance to the bacterial wilt. Four varieties: Rozovii Gigant, Krachodarskii Krasnii,Tarasenko and Lagidnii appeared to be resistant; Two varieties: Fakel and Polbig showed the moderate resistance and the rest ten varieties were susceptible to the disease.